Development of the green economy and increase of its impact on employment - MILITARU, Eva; STROE, Cristina; POPESCU, Silvia (Annals of Spiru Haret University. Economic Series, 2010)
The world economic recession caused the loss of jobs for 34 million people between the years 2008 and 2009, thus finding viable alternatives for job creation is a global priority. In this context, our work’s objective is to study the effects of green economy development on job creation at global level for the next decades. Based on a detailed documentary analysis, our paper will analyze the estimations regarding the number of jobs that will be created in one sector of the green economy, namely the renewable energy sector. Data prove that the renewable energy sector has a remarkable potential for job creation, the estimations showing that by carrying out smart policies for its support, massive investments would immediately follow and the number of jobs created in renewable energy sector could double in the next ten years and even triple in the next twenty years.